Analisis Ketersediaan Air dan Keandalan Kulong ST 12 Kecamatan Sungailiat Kabupaten Bangka sebagai Sumber Air Bersih Menggunakan Geographical Information System - Sisilia Jesika Pririzki; Hendy Stevanus; Rohil Agatha Lusia; Adriyansyah Adriyansyah (Universitas Negeri Gorontalo, 2022)
The Bangka Belitung Islands experience population growth which continues to increase every year. This population growth causes several problems, including water scarcity. The solution to this problem is to use water as a raw source to meet the need for clean water. The source of this raw water is by utilizing Kulong water. This study aims to find a solution by getting the location of the raw water source, namely Kulong, which has an effective distance from the location of community settlements. In this study, the mapping will be carried out using a Geographic Information System (GIS). The results of this study are that there is Kulong ST 12 which can be used as a source of raw water, and the best model for predicting water availability from 2022-2030 is the SARIMA (3,0,3) (3,1,0)12 model. The availability of water for Kulong ST 12 in 2030 is 10.03 l/s, with a water demand of 4.581 l/s in Surya Timur Village. For Reliability, Kulong ST 12, using the Standard Operating Rule (SOR), is able to supply 100% of the needs of the East Surya Output with a 100% reliability level.